Radiosurgery for Unruptured Brain Arteriovenous Malformations: An International Multicenter Retrospective Cohort Study. Issue 6 (20th April 2017) - Ding, Dale; Starke, Robert M.; Kano, Hideyuki; Lee, John Y.K.; Mathieu, David; Pierce, John; Huang, Paul; Missios, Symeon; Feliciano, Caleb; Rodriguez-Mercado, Rafael; Almodovar, Luis; Grills, Inga S.; et al.
Abstract: BACKGROUND: The role of intervention in the management of unruptured brain arteriovenous malformations (AVM) is controversial. OBJECTIVE: To analyze in a multicenter, retrospective cohort study, the outcomes following radiosurgery for unruptured AVMs and determine predictive factors. METHODS: We evaluated and pooled AVM radiosurgery data from 8 institutions participating in the International Gamma Knife Research Foundation. Patients with unruptured AVMs and ≥12 mo of follow-up were included in the study cohort. Favorable outcome was defined as AVM obliteration, no postradiosurgical hemorrhage, and no permanently symptomatic radiation-induced changes. RESULTS: The unruptured AVM cohort comprised 938 patients with a median age of 35 yr. The median nidus volume was 2.4 cm 3, 71% of AVMs were located in eloquent brain areas, and the Spetzler-Martin grade was III or higher in 57%. The median radiosurgical margin dose was 21 Gy and follow-up was 71 mo. AVM obliteration was achieved in 65%. The annual postradiosurgery hemorrhage rate was 1.4%. Symptomatic and permanent radiation-induced changes occurred in 9% and 3%, respectively. Favorable outcome was achieved in 61%. In the multivariate logistic regression analysis, smaller AVM maximum diameter ( P = .001), the absence of AVM-associated arterial aneurysms ( P = .001), and higher margin dose ( P = .002) were found to be independent predictors of a favorable outcome. A margin dose ≥ 20 Gy yielded a significantly higher rate of favorable outcome (70% vs 36%; P < .001) CONCLUSION: Radiosurgery affords an acceptable risk to benefit profile for patients harboring unruptured AVMs. These findings justify further prospective studies comparing radiosurgical intervention to conservative management for unruptured AVMs.